#### Answer

$4(x-3)(x+2)$

#### Work Step by Step

Factor out the GCF of $4$ to obtain:
$=4(x^2-x-6)$
The leading coefficient of the trinomial is 1.
Factor the trinomial by looking for factors of the constant term $(-6)$ whose sum is equal to the coefficient of the middle term $(-1)$.
Note that $-6=-3(2)$ and $-3+2=-1$.
This means that the factors we are looking for are $-3$ and $2$, and that the factored form of the trinomial is $(x-3)(x+2)$.
Thus, the completely factored form of the given polynomial is:
$=4(x-3)(x+2)$